Microstructure and electrical properties of solid electrolytes of fully stabilized zirconia with rare earth mixed oxides (2016)
In this work was obtained solid electrolytes of fully stabilized zircônia with doped of 10 and 12 mol% of Re2O3 (mixed oxides rare earth), for use in oxygen sensors and or fuel cells. The specimens were prepared by uniaxial pressing and sintered using two heating schedules, S1 and S2. Impedance diagrams show that the crystalline phases and the grain size change the electrical behavior of the ceramics. The sample with the best electrical performance was obtained with 10 mol% doped and was sintered with the curve S1. The value of the total conductivity of this sample was 2,85x10-3 W-1.cm-1 (taken at 600 ° C). When making a comparison between this values of conductivity with the reported in the literature is identified similarity with or traditional system zirconia-yttria the most widely used commercially as electrolyte oxygen sensors and fuel cells, confirming the potential use of the oxides mixed rare earth for these specific applications.